Woman’s Voice and The Author’s Social Background in The Book Bukan Salahmu Menjadi Perempuan - Aenun Azizah; Kurnia Rachmawati; Dicky Rachmat Pauji (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study examines the representation of women’s voices in Bukan Salahmu Menjadi Perempuan by Fajar Sulaiman by focusing on the relationship between the author’s social background and the construction of female experiences in the text. The research is motivated by the persistence of gender inequality and the emergence of literary works that articulate women’s emotional wounds, silence, and resilience. Employing a descriptive qualitative method, the study analyzes textual data through close reading and thematic categorization using Alan Swingewood’s sociology of the author as the main theoretical framework. The findings reveal that women’s voices are represented through themes of emotional suffering, social pressure, silencing, vulnerability, strength, and self-recovery. These representations are closely related to the author’s empathetic engagement with women’s lived experiences and his critical reflection on patriarchal social structures. The study concludes that the book functions not merely as a literary work but as a form of social testimony that reflects the dialectical relationship between the author and society, while simultaneously advocating gender awareness and empathy toward women’s experiences.